Electronic integration and thin film aspects of Au-Pd/rGO/TiO2 for improved solar hydrogen generation - Tudu, Bijoy; Nalajala, Naresh; Reddy, Kasala P.; Saikia, Pranjal; Gopinath, Chinnakonda S. (ACS Applied Materials & Interfaces, 2019)
In the present work, we have synthesized noble bimetallic nanoparticles (Au-Pd NPs) on a carbon-based support and integrated with titania to obtain Au-Pd/C/TiO2 and Au-Pd/rGO/TiO2 nanocomposites using an ecofriendly hydrothermal method. Here, a 1:1 (w/w) Au-Pd bimetallic composition was dispersed on (a) high-surface-area (3000 m(2) g(-1)) activated carbon (Au-Pd/C), prepared from a locally available plant source (in Assam, India), and (b) reduced graphene oxide (rGO) (Au-Pd/rGO); subsequently, they were integrated with TiO2. The shift observed in Raman spectroscopy demonstrates the electronic integration of the bimetal with titania. The photocatalytic activity of the above materials for the hydrogen evolution reaction was studied under 1 sun conditions using methanol as a sacrificial agent in a powder form. The photocatalysts were also employed to prepare a thin film by the drop-casting method. Au-Pd/rGO/TiO2 exhibits 43 times higher hydrogen (H-2) yield in the thin film form (21.50 mmol h(-1) g(-1)) compared to the powder form (0.50 mmol h(-1) g(-1)). On the other hand, Au-Pd/C/TiO2 shows 13 times higher hydrogen (H-2) yield in the thin film form (6.42 mmol h(-1) g(-1)) compared to the powder form (0.48 mmol h(-1) g(-1)). While powder forms of both catalysts show comparable activity, the Au-Pd/rGO/TiO2 thin film shows 3.4 times higher activity than that of Au-Pd/C/TiO2. This can be ascribed to (a) an effective separation of photogenerated electron-hole pairs at the interface of Au-Pd/rGO/TiO2 and (b) the better field effect due to plasmon resonance of the bimetal in the thin film form. The catalytic influence of the carbon-based support is highly pronounced due to synergistic binding interaction of bimetallic nanoparticles. Further, a large amount of hydrogen evolution in the film form with both catalysts (Au-Pd/C/TiO2 and Au-Pd/rGO/TiO2) reiterates that charge utilization should be better compared to that in powder catalysts.
Keywords: bimetal; Photocatalysis; surface plasmon resonance; TiO2; water splitting

Rationally designed, efficient, and earth-abundant Ni-Fe cocatalysts for solar hydrogen generation - Tudu, Bijoy; Nalajala, Naresh; Reddy, Kasala Prabhakar; Saikia, Pranjal; Gopinath, Chinnakonda S. (ACS Sustainable Chemistry & Engineering, 2021)
Developing highly efficient and affordable catalysts for solar hydrogen (H-2) generation is crucial, and employing a cocatalyst from earth-abundant elements has a critical role to play. In this context, different compositions of earth-abundant Ni-Fe alloy (1:1, 1:3, and 3:1) have been prepared by hydrothermal method; subsequently, 1 wt % of these Ni-Fe cocatalysts were integrated with TiO2-P25 and thoroughly characterized. The resultant catalysts have been evaluated for solar H-2 production, in powder and thin film forms, under one sun condition and in direct sunlight. Interestingly, all the catalysts in the thin film form exhibit superior hydrogen yield (HY), up to 27 times higher activity than its powder counterpart. Among the photocatalysts, Ni-Fe/TiO2 (3:1 = Ni/Fe; NFT31) composition exhibits the best HY in thin film (8.27 mmol.h(-1).g(-1)) and exceeds all other compositions of catalyst. It is also to be reported that HY measured for the powder form with 1 mg shows 3-17 times higher activity than that measured with 25 mg. This is mainly attributed to effective solar light absorption with a smaller amount of photocatalyst either spread over large area in a thin film form or well-dispersed in suspension forms. Furthermore, the enhanced activity obtained with Ni-Fe/TiO2 photocatalysts is also ascribed to strong electronic integration of Ni-Fe cocatalyst with TiO2 and higher performance obtained with a thin film is attributed to increased charge carrier generation and subsequent charge separation and effective utilization. A decrease in work function of TiO2 by 0.6 eV was observed after its integration with cocatalyst in NFT31.
Keywords: Cocatalyst; Hydrogen; Ni-Fe alloy; solar energy; TiO2; water splitting